FSG567: Polymer Production Process and Environment Impact / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This course enables students with sufficient chemical knowledge to gain an insight into molecular mechanism and develop knowledge of the control of reactions in the polymer industry. It demonstrates how polymer structural requirements are controlled in the polymer manufacturing industry. The students also discuss and resolve the complications related to the polymerization process and impact on environmental issues and social societies and their responsibilities to overcome them.